The Accuracy of Modified Gunter's Quadrant (Ver.2) in Prayer Time Calculation - M. Syaoqi Nahwandi; Ahmad Izzuddin (IJRAEL: International Journal of Religion Education and Law, 2022)
Gunter's Quadrant is the work of Edmund Gunter in modifying the Horary Quadrant but cannot be used to accommodate the needs of Muslims in knowing prayer times. In previous research, the author has developed the Modified Gunter's Quadrant (ver.1) which can be used for calculating prayer times and has succeeded in improving the basic design of Gunter's Quadrant so that it can be made for latitudes near the equator. However, the Modified Gunter's Quadrant (ver.1) produces curves that look broken and the accuracy of the calculation results still needs to be improved because the hour curves interval is 15 minutes. The method of research used is Development Research which becomes a further development of the Modified Gunter's Quadrant (ver.1) to eliminate deficiencies in the projection concept of the hour and azimuth curves and to improve the accuracy of the calculation results of prayer times. The result of this research is the Modified Gunter's Quadrant (ver.2) which has a better curve projection method and improved accuracy with hour curve intervals of 5 minutes. The results of the accuracy test show that the Modified Gunter's Quadrant (ver.2) deserves to be used as one of the classical instruments for calculating prayer times with a maximum error of 0h 0m 53s.